Processos de participação para o controle social em comissões locais de saúde: educar-se no cotidiano - Barbosa, Ana Maria Giusti (Universidade Federal de São Carlos, 2008)
In the set of the changes occurred in the Brazilian society since the promulgation of the Federal Constitution in 1988, lies the institutionalization of the society means of participation for purposes of social control on the public policies. Among these means are the Management Councils. In the health area, we can find Health Councils in national, state, city and local levels. Having the Knowledge that the Health Local Commissions, local modality of the Councils, are spaces where the social control and participation social practice occurs, and educative processes are broken out, built and configured according to circumstances and particularities of each of them, the following research question was made: "Which are the educative processes related to the participation exercise and social control experienced, generated, built and unchained in the Local Health Commissions?". This research had as purpose to understand the Health Local Commissions in the city of Piracicaba in São Paulo state regarding the educative processes experienced by its participants. The theoretical referential adopted was the Pedagogia Sócio-Cultural by Paulo Freire and Theory of quotidian by Michel Maffesoli. Methodologically, it consisted on a study of qualitative character based on contributions of the phenomenological theory for insertion in field and data analysis. The field research was made in the period of 2004 to 2007, comprising 14 Health Local Commissions of Piracicaba. The procedures used for data collection were the observations of the commissions functioning and interviews with the participants. Fifty four observation sessions, in which it was tried to collect the functioning dynamics, conflicts, tensions, feelings and emotions and identify the educative processes from the participants perception describing and analyzing them. Semi-structured interviews were made with 24 commissions participants (managers, workers and users) in which the participants perception on the educative processes were investigated. The bases of the interviews script were "insertion processes" and "participation". The data analysis emphasized the quotidian and educative processes using the following categories: participation, interaction, and social control on the public health policy. It was concluded that by means of participation, the people discovered new realities, accessed information, developed new perceptions and new abilities. They finished with the fear of exposing themselves and learned to express, give opinion, suggest, discuss, cooperate and creat strategies to accomplishing proposals. Such changes showed the possibility of learning about participation, interaction ande public policy: learn the pratice, learn practing and learn from the practice.
Keywords: Educação; Práticas sociais e processos educativos; Controle social; Cotidiano; Sistema Único de Sáude (Brasil); CIENCIAS HUMANAS::EDUCACAO